Risk assessment of banknotes as a fomite of SARS‐CoV‐2 in cash payment transactions. Issue 4 (1st May 2022) - Schijven, Jack F.; Wind, Mark; Todt, Daniel; Howes, John; Tamele, Barbora; Steinmann, Eike
Abstract: The COVID 19 pandemic has triggered concerns and assumptions globally about transmission of the SARS‐CoV‐2 virus via cash transactions. This paper assesses the risk of contracting COVID‐19 through exposure to SARS‐CoV‐2 via cash acting as a fomite in payment transactions. A quantitative microbial risk assessment was conducted for a scenario assuming an infectious person at the onset of symptoms, when virion concentrations in coughed droplets are at their highest. This person then contaminates a banknote by coughing on it and immediately hands it over to another person, who might then be infected by transferring the virions with a finger from the contaminated banknote to a facial mucous membrane. The scenario considered transfer efficiency of virions on the banknote to fingertips when droplets were still wet and after having dried up and subsequently being touched by finger printing or rubbing the object. Accounting for the likelihood of the scenario to occur by considering (1) a local prevalence of 100 COVID‐19 cases/100, 000 persons, (2) a maximum of about one‐fifth of infected persons transmit high virus loads, and (3) the numbers of cash transactions/person/day, the risk of contracting COVID‐19 via person‐to‐person cash transactions was estimated to be much lower than once per 39, 000 days (107 years) for a single person. In the general populace, there will be a maximum of 2.6 expected cases/100, 000 persons/day. The risk for a cashier at an average point of sale was estimated to be much less than once per 430 working days (21 months). The depicted scenario is a rare event, therefore, for a single person, the risk of contracting COVID‐19 via person‐to‐person cash transactions is very low. At a point of sale, the risk to the cashier proportionally increases but it is still low.